Dynamic analysis of three autoventilated disc brakes (2017)
The braking system of a car must meet several requirements, among which safety is the most important. It is also composed of a set of mechanical parts such as springs, different types of materials (Metallic and Non Metallic), gases and liquids. The brakes must work safely and predictably in all circumstances, which means having a stable level of friction, in any condition of temperature, humidity and salinity of the environment. For a correct design and operation of brake discs, it is necessary to consider different aspects, such as geometry, type of material, mechanical strength, maximum temperature, thermal deformation, cracking resistance, among others. Therefore, the main objective of this work is to analyze the dynamics and kinetics of the brake system from the pedal as the beginning of mathematical calculations to simulate the behavior and Analysis of Finite Elements (FEA), with the help of SolidWorks Simulation Software. The results show that the third brake disc works best in relation to the other two discs in their different working conditions such as speed and displacement in braking, concluding that depending on the geometry of the brake and the cooling channels these systems can be optimized that are of great importance for the automotive industry.